The Essential Guide to Semiconductors. - Turley, Jim (Essential Guide Ser., 2002)
The Essential Guide to Semiconductors is a complete guide to thebusiness and technology of semiconductor design and manufacturing. Conceptual enough for laypeople and nontechnical investors, yet detailedenough for technical professionals, Jim Turley explains exactly howsilicon chips are designed and built, illuminates key markets andopportunities, and shows how the entire industry "fits together."